The Arabidopsis SAL1-PAP Pathway: A Case Study for Integrating Chloroplast Retrograde, Light and Hormonal Signaling in Modulating Plant Growth and Development? - Phua, Su Y.; Yan, Dawei; Chan, Kai X.; Estavillo, Gonzalo M.; Nambara, Eiji; Pogson, Barry J. (Frontiers in Plant Science, 2018)
Plant growth and development are dependent on chloroplast development and function. Constitutive high level accumulation of a chloroplast stress signal, 3’-phosphoadenosine-5’-phosphate (PAP), confers drought tolerance to plants, but slow downs and alters plant growth and development. PAP, a by-product of sulfur metabolism, is maintained at very low levels by the SAL1 phosphatase during vegetative growth of Arabidopsis and accumulates in rosettes during drought and excess light. Eight independent forward genetic screens in Arabidopsis identified SAL1 as the regulator of multiple phenotypes related to stress responses, hormonal signalling and/or perception. In this perspective article, we collate all the sal1 phenotypes published in the past two decades, and distill the different pathways affected. Our meta-analysis of publicly available sal1 microarray data coupled to preliminary hormonal treatment and profiling results on sal1 indicate that homeostasis and responses to multiple hormones in sal1 are altered during rosette growth, suggesting a potential connection between SAL1-PAP stress retrograde pathway and hormonal signalling. We propose the SAL1-PAP pathway as a case study for integrating chloroplast retrograde signalling, light signalling and hormonal signalling in plant growth and morphogenesis.